Oral Management of a Haematopoietic Stem Cell Transplant Recipient with Chédiak–Higashi Syndrome - Kasumi Shimizu; Miho Hayashi; Nozomi Ito; Kokoro Hamada; Gaku Koizumi; Kazuto Kurohara; Naoya Arai (Case Reports in Dentistry)
Chédiak–Higashi syndrome (CHS), a rare autosomal recessive disorder associated with leukocyte dysfunction, is characterised by partial skin and hair albinism, immunodeficiency, and abnormal bleeding. Furthermore, it may be associated with cognitive and neurological impairments. The long-term prognosis of patients is generally poor, and haematopoietic stem cell transplantation is a radical immunodeficiency treatment. Here, we report a case of successful oral management of an 18-year-old woman with CHS accompanied by aggressive periodontitis who underwent haematopoietic stem cell transplantation.